2023
DOI: 10.3390/pharmaceutics15051456
|View full text |Cite
|
Sign up to set email alerts
|

Nanoplatforms Potentiated Ablation-Immune Synergistic Therapy through Improving Local Control and Suppressing Recurrent Metastasis

Abstract: Minimally invasive ablation has been widely applied for treatment of various solid tumors, including hepatocellular carcinoma, renal cell carcinoma, breast carcinomas, etc. In addition to removing the primary tumor lesion, ablative techniques are also capable of improving the anti-tumor immune response by inducing immunogenic tumor cell death and modulating the tumor immune microenvironment, which may be of great benefit to inhibit the recurrent metastasis of residual tumor. However, the short-acting activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…(6) The patient has not received any other antitumor therapy, including radiotherapy, TACE, and targeted drugs, prior to this treatment. (7) Child-Pugh grade A or B, with no current encephalopathy or ascites (small amount). ( 8) Left ventricular ejection fraction is ≥50%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(6) The patient has not received any other antitumor therapy, including radiotherapy, TACE, and targeted drugs, prior to this treatment. (7) Child-Pugh grade A or B, with no current encephalopathy or ascites (small amount). ( 8) Left ventricular ejection fraction is ≥50%.…”
Section: Methodsmentioning
confidence: 99%
“…4,5 Studies conducted both domestically and internationally have demonstrated that RFA is capable of killing HCC cells while also stimulating targeted antitumor immune responses. [6][7][8] Therefore, the anti-tumor immune mechanism of RFA is becoming a new research hotspot in the field of HCC. 9 Although RFA has the potential to boost the antitumor immune response in HCC patients, typically the resulting immune response is insufficient to prevent tumor recurrence.…”
Section: Introductionmentioning
confidence: 99%